Recombinant human platelet-derived growth factor-BB combined with grafting materials for the treatment of periodontal intrabony defects: a meta-analysis - Hao, Wensong; Leilei, Li; Kun, Huang; Sui, Xiaodong; Qi, Yuanyuan (Vojnosanitetski pregled, 2025)
Background/Aim. Periodontitis is a common dental disease affecting around 50% of adult patients globally. It can cause continuous deterioration of periodontal tissue inflammation, leading to irreversible periodontal bone resorption and even tooth loosening. Currently, suitable techniques for managing periodontal intrabony deformities include both allogeneic and autologous bone transplantation, but these methods have certain limitations. The aim of this study was to examine the effect of recombinant human platelet-derived growth factor-BB (rhPDGF-BB) in combination with grafting materials for the treatment of periodontal intraosseous defects using a meta-analysis. Methods. In March 2024, electronic databases (Cochrane Library, PubMed, Embase, Web of Science) were searched to gather data from studies on growth factors and grafting materials for the treatment of intrabony periodontal deficiencies. Results. A total of 11 articles were fully reviewed, of which nine were included in the meta-analysis. The 9 studies included 313 people, divided into two groups: experimental (n = 156) and control (n = 157). The results of the meta-analysis indicate significantly higher clinical attachment level (CAL) of the experimental group [p < 0.01, standardized mean difference (SMD): 0.80; 95% confidence interval (CI): 0.49, 1.10] compared to the control group. Changes in probing depth (PD) of the experimental group were greater (p
Keywords: database; meta-analysis; periodontal diseases; platelet-derived growth factor